2021
DOI: 10.1186/s12992-021-00748-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the impact of trade agreements on national food environments: the case of Vanuatu

Abstract: Background A large body of literature exists on trade liberalisation and the ways in which trade agreements can affect food systems. However, the systematic and objective monitoring of these and their impact on national food environments has been limited. Using a case study, this paper undertakes a systematic analysis of how Vanuatu’s obligations under WTO agreements has impacted its food environment. Results Data collection was guided by the INFOR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For example, trade policies and their impacts on processed food consumption dominated early literature on dietary transition in PICs and continues to be a key focus of research in this area. Studies found that trade liberalization, in particular, resulted not only in greater imports of ultra-processed foods but also that the ensuing competition caused a reduction in the prices of domestically-produced processed foods in low- to middle-income PICs, ultimately making processed food more affordable within Pacific communities (e.g., [ 13 , 14 , 15 , 16 ]). Nutrition reports from PICs also confirm an increase in the consumption of processed foods, including refined cereals, sugar-sweetened beverages, meat, and fats, after trade polices (including trade liberalization) came into effect in PICs (e.g., [ 12 , 14 , 15 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, trade policies and their impacts on processed food consumption dominated early literature on dietary transition in PICs and continues to be a key focus of research in this area. Studies found that trade liberalization, in particular, resulted not only in greater imports of ultra-processed foods but also that the ensuing competition caused a reduction in the prices of domestically-produced processed foods in low- to middle-income PICs, ultimately making processed food more affordable within Pacific communities (e.g., [ 13 , 14 , 15 , 16 ]). Nutrition reports from PICs also confirm an increase in the consumption of processed foods, including refined cereals, sugar-sweetened beverages, meat, and fats, after trade polices (including trade liberalization) came into effect in PICs (e.g., [ 12 , 14 , 15 , 17 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In the period the WHO commissioned various projects to combat obesity, free trade agreements (FTAs) which the WTO oversees, increased to 270 in 2017 in less than 30 years, and obesity rose from 4% to over 18% in the corresponding period [39]. Evidence shows that the proliferation of FTAs is associated with increased sugar and calorie consumption [39,40], demonstrating the global north's heavy influence in the governance and set up of WTO. This governance set-up pushes capitalist ideas and policies that further the global north's goals without concern for the health of the global south [39,40].…”
Section: Current Global Health Governance Response To Obesitymentioning
confidence: 99%
“…Evidence shows that the proliferation of FTAs is associated with increased sugar and calorie consumption [39,40], demonstrating the global north's heavy influence in the governance and set up of WTO. This governance set-up pushes capitalist ideas and policies that further the global north's goals without concern for the health of the global south [39,40]. While the WHO's policy actions against obesity may have called for inter/multi-sectoral cooperation, the reality is that cooperation among the major players in the GHG space has been anything but that [39,40].…”
Section: Current Global Health Governance Response To Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…It represents an effective means to maintain quality of meat and extend its shelf life, especially during long-distance transportation. For this reason, most categories of meat in international trade are in frozen form (Ravuvu et al, 2021). Moreover, consumers also prefer keeping products in a frozen state at home.…”
Section: Introductionmentioning
confidence: 99%